3D measurements and motion analysis supported by passive vision techniques - Kohut, Piotr (Computer Assisted Methods in Engineering and Science, 2007)
The article contains presentation of application of three-dimensional vision methods in realization of vibration easurements and their analysis. For this purpose algorithms were developed of discrete epipola geometry and structure from motion, with the usage of one camera. Vibration amplitude is determined for selected measurement points on the analyzed object. Each point is represented by flat or three-dimensional marker attached on a construction. The article includes algorithms of the discussed methods and verification of those methods based upon simulation data, as we as preliminary experimental tests carried out on a test bed.